Decision-making in localized prostate cancer: lessons learned from an online support group - Huber, Johannes; Ihrig, Andreas; Peters, Tim; Huber, Christian G.; Keßler, Anja; Hadaschik, Boris; Pahernik, Sascha; Hohenfellner, Markus (BJU international, 2011)
Study Type ? Patient (preference/ecological) ?Level of Evidence?2c What's known on the subject? and What does the study add? Social support plays a major role for decision-making in localized prostate cancer and the importance of online resources has become increasingly recognized. However, so far most of the knowledge has been generated on formal and stylistic aspects. The study adds to understanding the content and the dynamics of peer-to-peer counselling in an online support group. OBJECTIVE ??To investigate patient-to-patient communication with regard to decision-making in localized prostate cancer; as most of it is done in private, online support groups are a unique means for this task. PATIENTS AND METHODS ??Over a 32-month period, we screened 501 threads in the largest German online support group for prostate cancer. ??Threads started by questioners newly diagnosed with localized prostate cancer and stating decision-making as the key topic were included; in all, 82 (16.4%) threads met these criteria. ??Two independent investigators characterized every thread following a standardized protocol. ??Fisher?s exact test and Mann?Whitney U-test were applied for group analyses. A complementary qualitative linguistic approach was chosen. RESULTS ??Threads were most commonly started to ask for therapy recommendations (66%), information on the course of treatment (46%) and emotional support (46%). ??Answers consisted of treatment recommendations (40%), emotional support (37%) and personal experiences (28%). ??A second opinion on the biopsy cores (51%) and additional imaging (40%) were common suggestions. ??The rate of advice for radical prostatectomy (RP) vs radiotherapy was 67 vs 82%. Thus, surgery was less recommended in our sample (P= 0.01); 75% of the men with an initial therapeutic preference were finally confirmed herein. ??Linguistic analysis showed that posters frequently use a tentative language style and that common language is avoided. CONCLUSIONS ??Patients readily receive information, advice and emotional support as part of an online support group. ??The scientific evaluation of an online support group is a complementary way of getting to know our patients? needs and worries. ??Patient?physician contact can benefit from this knowledge.